The Dendritic Cell Therapy for Complication of Type 2 Diabetes Mellitus - Jonny; Yana, Martina Lily; Pramono, Ardianto; Drajat, Endang; Setiawan, Erwin; Dimu, Paulus Stefanus; Kapusin, Ernaldi; Putranto, Terawan Agus; Lister, I Nyoman Ehrich; Ginting, Chrismis Novalinda; Farhat; Icksan, Aziza Ghanie; et al. (PUBLIS PENERBIT UNPRI PRESS, 2025)
Praises be to God Almighty that we have been able to complete this book, The Dendritic Cell Therapy for Complications of Type 2 Diabetes Mellitus. This book presents a collection of research studies focused on the potential of autologous dendritic cell therapy in addressing complications associated with type 2 diabetes mellitus. Type 2 diabetes mellitus is known to cause both macrovascular and microvascular complications. This book concentrates specifically on microvascular complications, with a particular focus on diabetic kidney disease and diabetic neuropathy—two of the most prevalent and debilitating conditions affecting patients with type 2 diabetes. The research compiled herein aims to explore and expand the therapeutic potential of autologous dendritic cells in mitigating these complications. We would like to extend our sincere gratitude to all contributors who shared their ideas, insights, and dedication in support of the studies featured in this book. A total of seven original research contributions are included, each authored by committed, passionate researchers. We are also deeply grateful to Prof. Dr. dr. Terawan Agus Putranto, Sp.Rad(K) RI, and Prof. I Nyoman Ehrich Lister, M.Kes, AIFM, Sp.KKLP, for their generous forewords and support throughout the journey of writing this book. Finally, we would like to thank all individuals and institutions who lent their time, energy, and expertise in the preparation of this publication. It is our hope that this book will serve as a meaningful contribution to the scientific community and support the advancement of medical research and innovation in Indonesia and beyond.